Changes in Kinematics and Muscle Activity With Increasing Velocity During Underwater Undulatory Swimming - Yamakawa, Keisuke Kobayashi; Shimojo, Hirofumi; Takagi, Hideki; Sengoku, Yasuo (Frontiers in Sports and Active Living, 2022)
This study aimed to investigate the changes in kinematics and muscle activity with increasing swimming velocity during underwater undulatory swimming (UUS). Eight male national-level swimmers performed three UUS trials at 70%, 80%, and 90% of their maximum swimming velocity (70%V, 80%V and 90%V, respectively) in a water flume. A motion capture system was used for three-dimensional kinematic analysis, and surface electromyography (EMG) data were collected from eight muscles in the gluteal region and lower limbs. The results indicated that kick frequency, vertical toe velocity, and angular velocity increased with increasing UUS velocity, whereas kick length and kick amplitude decreased. Furthermore, the symmetry of the peak toe velocity improved at 90%V. The integrated EMG values of the rectus femoris, biceps femoris, gluteus maximus, gluteus medius, tibialis anterior, and gastrocnemius were higher at 90%V than at the lower flow speeds, and the sum of integrated EMGs increased with increasing UUS velocity. These results suggest that an increase in the intensity of muscle activity in the lower limbs contributed to an increase in kick frequency. Furthermore, muscle activity of the biceps femoris and gastrocnemius commenced slightly earlier with increasing UUS velocity, which may be related to improving kick symmetry. In conclusion, this study suggests the following main findings: 1) changes in not only kick frequency but also in kicking velocity are important for increasing UUS velocity, 2) the intensity of specific muscle activity increases with increasing UUS velocity, and 3) kick symmetry is related to changes in UUS velocity, and improvements in kick symmetry may be caused by changes in muscle activity patterns.